(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The article is devoted to the analysis of a derived word from the position of conceptual blending theory. The ability of a derivative word to convey human knowledge about the world and objectify propositional structures gives the right to define a derivative word as a cognitive structure that transmits knowledge and generates new meanings. In this respect, it can be studied from the position of conceptual blending theory